The Role of Ecotourism in Supporting Biodiversity Conservation in National Park Areas - Erina Ermayanti; Duyen Thi Thu Tran; Rajdeep Deb (Lembaga Penelitian dan Pendidikan, 2026)
Ecotourism has become an important strategy for supporting biodiversity conservation and sustainable development in national park areas. The increasing global demand for nature-based tourism encourages national park managers to balance environmental protection with tourism development. This study aims to analyze the role of ecotourism in supporting biodiversity conservation in national park areas and examine its socio-economic and environmental contributions to local communities and protected ecosystems. The research employed a qualitative descriptive approach through literature review and comparative analysis of previous studies related to ecotourism, biodiversity conservation, and sustainable tourism management. The findings indicate that ecotourism contributes positively to biodiversity conservation by increasing environmental awareness, generating conservation funding, supporting habitat protection, and encouraging community participation in conservation activities. In addition, ecotourism creates alternative economic opportunities for local communities through employment, tourism services, and sustainable resource management. However, uncontrolled tourism activities may also generate environmental pressures such as habitat degradation, waste accumulation, and wildlife disturbance. Therefore, sustainable ecotourism management strategies emphasizing community involvement, visitor management, environmental education, and conservation-oriented policies are essential for maintaining ecological balance within national park areas. This study contributes to sustainable tourism literature by strengthening the understanding of ecotourism as an integrated approach to biodiversity conservation and sustainable regional development.